Paternal unemployment during childhood: Causal effects on youth worklessness and educational attainment - Steffen Mueller; Regina T. Riphahn; Caroline Schwientek (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2014)
Using long-running data from the German Socio-Economic Panel (1984-2012) we investigate the impact of paternal unemployment on child labor market and education outcomes. We first describe correlation patterns and then use sibling fixed effects and the Gottschalk (1996) method to identify the causal effects of paternal unemployment. We find different patterns for sons and daughters. Paternal unemployment does not seem to causally affect the outcomes of sons. In contrast, it increases both daughters' worklessness and educational attainment. We test the robustness of the results and explore potential explanations.
Keywords: J62; C21; C26; 330; youth unemployment; educational attainment; intergenerational mobility; causal effect; Gottschalk method; sibling fixed effects